Genome-wide association study of sporadic brain arteriovenous malformations. Issue 9 (27th January 2016) - Weinsheimer, Shantel; Bendjilali, Nasrine; Nelson, Jeffrey; Guo, Diana E; Zaroff, Jonathan G; Sidney, Stephen; McCulloch, Charles E; Al-Shahi Salman, Rustam; Berg, Jonathan N; Koeleman, Bobby P C; Simon, Matthias; Bostroem, Azize; et al.
Abstract : Background: The pathogenesis of sporadic brain arteriovenous malformations (BAVMs) remains unknown, but studies suggest a genetic component. We estimated the heritability of sporadic BAVM and performed a genome-wide association study (GWAS) to investigate association of common single nucleotide polymorphisms (SNPs) with risk of sporadic BAVM in the international, multicentre Genetics of Arteriovenous Malformation (GEN-AVM) consortium. Methods: The Caucasian discovery cohort included 515 BAVM cases and 1191 controls genotyped using Affymetrix genome-wide SNP arrays. Genotype data were imputed to 1000 Genomes Project data, and well-imputed SNPs (>0.01 minor allele frequency) were analysed for association with BAVM. 57 top BAVM-associated SNPs (51 SNPs with p<10 -05 or p<10 −04 in candidate pathway genes, and 6 candidate BAVM SNPs) were tested in a replication cohort including 608 BAVM cases and 744 controls. Results: The estimated heritability of BAVM was 17.6% (SE 8.9%, age and sex-adjusted p=0.015). None of the SNPs were significantly associated with BAVM in the replication cohort after correction for multiple testing. 6 SNPs had a nominal p<0.1 in the replication cohort and map to introns in EGFEM1P, SP4 and CDKAL1 or near JAG1 and BNC2 . Of the 6 candidate SNPs, 2 in ACVRL1 and MMP3 had a nominal p<0.05 in the replication cohort. Conclusions: We performed the first GWAS of sporadic BAVM in the largest BAVM cohort assembled to date. No GWAS SNPs were replicated, suggesting that common SNPs do not contribute strongly to BAVM susceptibility. However, heritability estimates suggest a modest but significant genetic contribution.